A compendium of world sovereigns. - Venning, Timothy, author.
1 online resource (x, 348 pages)
Keywords: The Compendium of World Sovereigns series contains three volumes: Ancient, Medieval, and Early Modern. These volumes provide students with easy-to-access ⁰́₈who⁰́₉s who⁰́₉ with details on the identities and dates, ages and wives, where known, of heads of government in any given state at any time within the framework of reference. The relevant original and secondary sources are also listed in a comprehensive bibliography. Providing a clear reference guide for students, to who was who and when they ruled in the dynasties and other ruler-lists for the Ancient, Medieval, and Early Modern worlds ⁰́₃ primarily European and Middle Eastern but including available information on Africa and Asia and the pre-Columbian Americas. The trilogy accesses and interprets the original data plus any modern controversies and disputes over names and dating, reflecting on the shifts and widening of focus in student and academic studies. Each volume contains league tables of rulers⁰́₉ ⁰́₈records⁰́₉, and an extensive bibliographical guide to the relevant personnel and dynasties, plus any controversies, so readers can consult these for extra details and know exactly where to go for which information. All relevant information is collected and provided as a one-stop-shop for students wishing to check the known information about a world Sovereign. The Ancient volume begins with the Pharaohs in Egypt and moves through Greece, Classical and Early Medieval Armenia, Crimea, Syria, Jordan, Israel and Judah, Persia, India and ends with the Roman World in the east and west. A Compendium of World Sovereigns: Volume I Ancient provides students and scholars with the perfect reference guide to support their studies and to fact check dates, people, and places.